2019
DOI: 10.1101/596940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human-specific paralogs SRGAP2B and SRGAP2C differentially modulate SRGAP2A-dependent synaptic development

Abstract: Human-specific gene duplications (HSGD) have recently emerged as key modifiers of brain development and evolution. However, the molecular mechanisms underlying the function of HSGDs remain often poorly understood. In humans, a truncated duplication of SRGAP2A led to the emergence of two human-specific paralogs: SRGAP2B and SRGAP2C. The ancestral copy SRGAP2A limits synaptic density and promotes maturation of both excitatory (E) and inhibitory (I) synapses received by cortical pyramidal neurons (PNs). SRGAP2C b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We would like to thank Dr. Edward Ruthazer for valuable input throughout the course of this study, as well as Dr. Andrew Greenhalgh and Andy YL Gao for a critical review of the manuscript. A version of this article has been released as a bioRxiv preprint at: https://doi.org/10.1101/742148 (Salmon et al, 2019).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…We would like to thank Dr. Edward Ruthazer for valuable input throughout the course of this study, as well as Dr. Andrew Greenhalgh and Andy YL Gao for a critical review of the manuscript. A version of this article has been released as a bioRxiv preprint at: https://doi.org/10.1101/742148 (Salmon et al, 2019).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Co-expression in COS7 cells revealed that SRGAP2C also interacts with SRGAP2A via their F-BAR domain resulting in degradation of the heterodimer product in a proteasome-dependent manner (Schmidt et al, 2019), explaining the mirroring effect between Srgap2-knockdown and SRGAP2C-expressing mice. Moreover, SRGAP2A promotes maturation of excitatory and inhibitory synapses through interaction with key molecular players such as Homer, Gephyrin, and Rac1; functions that are inhibited in the presence of SRGAP2C, leading to delayed neuronal maturation and a higher density of synapses (both excitatory and inhibitory) (Fossati et al, 2016;Schmidt et al, 2019). Further, expression of SRGAP2C in mouse cortical pyramidal neurons resulted in increased long-range synaptic connectivity (Schmidt et al, 2021).…”
Section: Srgap2cmentioning
confidence: 98%
“…Finally, Srgap2, which is downregulated in P07 HU mice, inhibits dendrite branching and synaptogenesis (Charrier et al, 2012). Human-specific duplication of SRGAP2C suppresses activity of SRGAP2, resulting in complex dendrites and a greater density of spines in human (Schmidt et al, 2019;Schmidt et al, 2021).…”
Section: Human Clock Regulates Genes With Human-specific Open Chromatinmentioning
confidence: 99%